Research on Modeling Crystallographic Texture Evolution of Al Alloy 7075 - Liu, Hao; Zhao, Man; Zhou, Yufeng; Liu, Gang (Frontiers in Materials, 2021)
Crystallographic texture is related to the anisotropy or isotropy of material physical properties, including mechanical performance. The crystallographic effect in micro-machining is more significant than that in macro-processing owing to that the depth of cut and the grain size are in the same order. It is of great significance to model the crystallographic texture evolution induced by mechanical and thermal load during micro-machining to investigate the surface integrity and performance of finished product. This paper performed hot deformation experiments of Al alloy 7075 (AA7075) under various input parameters, including temperature, temperature rate, stain rate and strain, which designed using Taguchi-method. Following that, crystallographic orientation of the samples before and after the deformation were test using Electron Back-Scattered Diffraction (EBSD). Then, the crystallographic texture evolution were modeled with the parameters obtained by fitting part of experimental data. The Crystallographic texture evolution of AA7075 under different levels of input parameters is studied and analyzed. Finally, the sensitivity of crystallographic orientation evolution to the process parameter are analyzed. The results indicate that these four input parameters have a significant impact on some crystallographic texture of the specimens. The proposed model is instructive in the future investigation of micro-machining and microstructure evolution.